Hydrogenation of 2-ethylanthraquinone with monolithic catalysts: An experimental and modeling study. (23rd November 2017) - Guo, Yanyan; Dai, Chengna; Lei, Zhigang
Highlights: A series of monolith catalysts were prepared, characterized and evaluated. Pd/MCM-41/COR was superior to commercial Pd-based pellet catalysts. Mass transfer under different operating and structural parameters was analyzed. Chemical reaction can enhance the mass transfer in monolith catalysts. Abstract: A series of Pd/zeolite/cordierite (zeolite = MCM-41, SBA-15, Beta, or MCM-22; cordierite = COR) monolithic catalysts, as well as Pd/ZIF-8/COR, Pd/Al2 O3 /COR, and Pd/SiO2 /COR, were prepared, characterized, and evaluated for the hydrogenation of 2-ethylanthraquinone (eAQ) to 2-ethyl-9, 10-anthrahydroquinone (eAQH2 ). We found that a 0.8% Pd/MCM-41/COR catalyst exhibited the highest H2 O2 yield (7.54 g L −1 ) and selectivity (85.3%) toward active quinones for hydrogen peroxide (H2 O2 ) production using the anthraquinone method. Notably, the Pd efficiency (1573 gH2 O2  g −1 Pd h −1 ) for the 0.8% Pd/MCM-41/COR monolithic catalyst was much higher than that of a commercial pellet catalyst (500 gH2 O2  g −1  Pd h −1 ). The intrinsic kinetics of hydrogenation of eAQ over 0.8% Pd/MCM-41/COR was measured, and the kinetic equation parameters were incorporated into a computational fluid dynamics (CFD) model. The mass transfer coefficients for the monolithic catalysts are 5–20 times higher than the pelleted catalyst. In addition, we found that the gas-liquid mass transfer is the controlling step, showing the unique advantages of monolithic catalysts for process intensification.